Abortion policy implementation in Ireland: successes and challenges in the establishment of hospital-based services - Bianca M. Stifani; Joanna Mishtal; Wendy Chavkin; Karli Reeves; Lorraine Grimes; Dyuti Chakravarty; Deirdre Duffy; Mark Murphy; Trish Horgan; Mary Favier; Antonella Lavelanet (Elsevier, 2022)
Objective: To describe successes and highlight remaining challenges in the establishment of hospital-based abortion services after legal change in the Republic of Ireland. Methods: We conducted a mixed-methods study on the implementation of abortion policy in Ireland. In this manuscript, we present the results from a qualitative analysis of in-depth interviews conducted with hospital-based providers, service users, and key informants. We used Dedoose software to conduct a thematic analysis of the data. Results: We report findings from interviews with 28 obstetrician gynecologists, midwives, psychiatrists, anesthesiologists, and nurses; a subset of 7 service users who sought care in hospitals; and 27 key informants. In this analysis, we describe how key themes that pertain to information, capacity and power, facilitated and hindered the implementation of hospital-based abortion services. We found that individual champions are key to establishing the service, but their motivation is not always sufficient to integrate abortion into existing clinical services, and conscientious objection is a persistent barrier to expanding abortion services. The main challenges highlighted here are lack of abortion provision at some hospitals and limited access to surgical abortion at most hospitals due to provider-level, logistical, and infrastructure barriers. Conclusions: This study presents new information on how abortion policy is implemented on the ground in hospital settings. Its findings can inform public health officials and providers in Ireland and other countries wishing to establish abortion services.